Раздельный сбор твердых бытовых отходов: опыт и перспективы в Украине - Тихомирова, Татьяна Сергеевна; Быканов, Сергей Николаевич; Горбунова, Ольга Владимировна (НТУ "ХПИ", 2017)
У статті розглянуті основні економічні та соціальні складові, що впливають на повільне поширення роздільного збору твердихпобутових відходів в Україні вцілому і в Харківській області зокрема. Проаналізовано дані власних досліджень про причини, які негативно впливають на впровадження роздільного збору побутового сміття в Харківській області. Запропоновано реальні економічні і соціальні важелі для вирішення поставленої проблеми.

The main economic and social components that influence the slow spreading of separate collection of household waste in Ukraine in general and in the Kharkiv region in particular is considered. The data of own researches about the reasons which negatively influence introduction of separate gathering of household dust in the Kharkov area are analyzed. Real economic and social levers are proposed to solve the problem.
Household wastes separating: experience and prospects in Ukraine
Keywords: ТБО; полимерные отходы; вторичная переработка; вторсырье; мусор; функциональный состав